2023
DOI: 10.1111/mec.17049
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics reduce Pocillopora coral‐associated bacteria diversity, decrease holobiont oxygen consumption and activate immune gene expression

Abstract: Corals are important models for understanding invertebrate host-microbe interactions; however, to fully discern mechanisms involved in these relationships, experimental approaches for manipulating coral-bacteria associations are needed.Coral-associated bacteria affect holobiont health via nutrient cycling, metabolic exchanges and pathogen exclusion, yet it is not fully understood how bacterial community shifts affect holobiont health and physiology. In this study, a combination of antibiotics (ampicillin, stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 145 publications
2
4
0
Order By: Relevance
“…It is likely that our colony forming unit assay, which allowed us to show that bacterial load is reduced in treated anemones, missed key bacterial groups that remain refectory to cultivation on marine agar. However, our results are consistent with previous work in cnidarians which showed that antibiotics reduced the abundance of bacteria within the host microbiome following 5–7 days of exposure ( 33 , 35 , 46 , 47 ). Surprisingly, our community composition analysis revealed that the microbiome only shifted in treated anemones during recovery.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It is likely that our colony forming unit assay, which allowed us to show that bacterial load is reduced in treated anemones, missed key bacterial groups that remain refectory to cultivation on marine agar. However, our results are consistent with previous work in cnidarians which showed that antibiotics reduced the abundance of bacteria within the host microbiome following 5–7 days of exposure ( 33 , 35 , 46 , 47 ). Surprisingly, our community composition analysis revealed that the microbiome only shifted in treated anemones during recovery.…”
Section: Discussionsupporting
confidence: 93%
“…1 ). The priming stage enables the initial depletion of the Aiptasia microbiome ( 43 ), while exposure to each of the antibiotic solutions during the treatment phase helps to reduce the cnidarian microbial load ( 33 , 35 , 42 , 47 ). Throughout the experiment, anemones were reared in six-well plates at 25°C and 12 h light:12 h dark cycle using 44 ± 15 µmol photon/m 2 /s light levels, in either artificial seawater (ASW; control group; Coral Pro Red Sea Salt Salinity 35 ppt) or 0.2 µm filtered artificial seawater (FASW; treatment groups).…”
Section: Methodsmentioning
confidence: 99%
“…In our study, we showed that antibiotic solutions decreased the microbial load and composition of the Aiptasia microbiome. Our primary finding is consistent with previous work in cnidarians which showed that antibiotics reduced the abundance of bacteria within the host microbiome following 5-7 days of exposure (31,33,43,44). Surprisingly, our community composition analysis revealed that the microbiome only shifted in treated anemones during recovery.…”
Section: Antibiotic Exposure Reduced Bacterial Load Up To One-week Po...supporting
confidence: 92%
“…1A). The priming stage enables the initial depletion of the Aiptasia microbiome (40), while exposure to each of the antibiotic solutions during the treatment phase helps to reduce the cnidarian microbial load (31,32,44,50).…”
Section: Methodsmentioning
confidence: 99%
“…Zhongshania (ASV 23) is dominant in sediments and seawater polluted with crude oil and aromatic compounds, and potentially degrade alkane and aromatics, respectively [ 47 , 48 ]. The bacteria in the genus Kordiimonas (ASV 27 and 38) are common within coral holobiont and are thought to be one of the bacteria with important functions [ 49 ]. Aliikangiella (ASV 41) had a differentially abundant ASV in large size oysters than in small size oysters, indicating that it appears to have roles in nutrient absorption and energy acquisition [ 50 ].…”
Section: Discussionmentioning
confidence: 99%